Validation of CCAPS-Indo for Indonesian High School Students - Susi Fitri; Dede Rahmat Hidayat; Bagus Julian Hikmy (Journal of Educational Studies, 2026)
Mental health problems among Indonesian high school students may interfere with academic functioning, social adjustment, and overall well-being, yet schools still lack multidimensional instruments that are culturally appropriate for early identification. This study aimed to adapt and validate the Indonesian version of the Counseling Center Assessment of Psychological Symptoms (CCAPS-Indo) for use with high school students. The original CCAPS-62 was translated, back-translated, and reviewed for cultural relevance before psychometric testing. Data were collected from 450 students enrolled in senior high schools and vocational high schools in Jakarta, Indonesia. Construct validity was examined using second-order confirmatory factor analysis, while composite reliability and average variance extracted were used to evaluate reliability and convergent validity. The refined model retained 42 items across eight dimensions. Most model-fit indices indicated acceptable to good fit, including ?2/df, GFI, CFI, TLI, NFI, IFI, RMSEA, and SRMR, although AGFI remained below the preferred threshold. Standardized loading factors for retained items ranged from 0.55 to 0.98, and composite reliability values ranged from 0.66 to 0.91. These findings suggest that the CCAPS-Indo demonstrates acceptable psychometric performance for assessing psychological symptoms among Indonesian high school students. The instrument may therefore be used as a school-based screening tool to support early identification and intervention, although further validation with broader and more diverse samples is still needed